2018
DOI: 10.1158/1541-7786.mcr-18-0114
|View full text |Cite
|
Sign up to set email alerts
|

Digital PCR-Based T-cell Quantification–Assisted Deconvolution of the Microenvironment Reveals that Activated Macrophages Drive Tumor Inflammation in Uveal Melanoma

Abstract: : Uveal melanoma progression can be predicted by gene expression profiles enabling a clear subdivision between tumors with a good (class I) and a poor (class II) prognosis. Poor prognosis uveal melanoma can be subdivided by expression of immune-related genes; however, it is unclear whether this subclassification is justified; therefore, T cells in uveal melanoma specimens were quantified using a digital PCR approach. Absolute T-cell quantification revealed that T-cell influx is present in all uveal melanomas a… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
31
1

Year Published

2019
2019
2022
2022

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 37 publications
(35 citation statements)
references
References 36 publications
1
31
1
Order By: Relevance
“…Further evidence for a better efficacy of the combined regimen is supported by the observation of complete responders, albeit to a small extent. This is notable as UM is considered a "cold" tumor due to a low mutational burden and a unique immunosuppressive tumor microenvironment [27][28][29]. Further research is urgently needed to identify the radiologic, immunologic, and molecular determinants for treatment response in this small subset of patients.…”
Section: Discussionmentioning
confidence: 99%
“…Further evidence for a better efficacy of the combined regimen is supported by the observation of complete responders, albeit to a small extent. This is notable as UM is considered a "cold" tumor due to a low mutational burden and a unique immunosuppressive tumor microenvironment [27][28][29]. Further research is urgently needed to identify the radiologic, immunologic, and molecular determinants for treatment response in this small subset of patients.…”
Section: Discussionmentioning
confidence: 99%
“…Although higher cytotoxic expression patterns are associated with better anti-tumor response and better patient survival in many solid tumors [34,41,42], the prognostic effects of immune infiltration depend on the type of tumor, the location of the cells and the state of activation. In UM, high levels of immune cells are associated with poor prognostic factors, such as M3 and BAP1 mutation [15,17,43]. Immune cell infiltration occurs more frequently in epithelioid-cell-type UM, which also has a poor prognosis [44].…”
Section: Discussionmentioning
confidence: 99%
“…Moreover, one of the most significant UM studies revealed that lymphocyte infiltration and tumorassociated M2 macrophage levels were associated with a poor prognosis in primary UM after adjustment for other risk factors [16]. In another study, the authors used a digital PCR-based T cell quantification method to characterize the prognostic value of the T cell count and activated macrophage level in the microenvironment of UM [17]. Thus, characterizing the immunological features of UM may provide novel immune biomarkers for prognostic assessment and immunotherapy.…”
Section: Introductionmentioning
confidence: 99%
“…Previous studies mainly focused on the intrinsic genes of tumors [ 19 ], and some have provided elegant analyses on expression of immune-related genes or immune-infiltration in UM [ 11 , 20 ]. However, a comprehensive analysis of the UM microenvironment consisting of larger cohorts is needed in studies of the UM microenvironment.…”
Section: Discussionmentioning
confidence: 99%